Popular cinemas in East Central Europe : film cultures and histories - Pitassio, Francesco; Varga, Zsuzsanna; Ostrowska, Dorota, 1973-; Pitassio, Francesco; Varga, Zsuzsanna (International library of the moving image, 2017)
The continued interest in the social and cultural life of the former Warsaw pact countries - looking at but also beyond their socialist pasts - encompasses a desire to know more about their national cinemas. Yet, despite the increasing consumption of films from these countries - via DVD, VOD platforms and other alternative channels - there is a lack of comprehensive information on this key aspect of visual culture. This important book rectifies the glaring gap and provides both a history and a contemporary account of East Central European cinema in the pre-WW2, socialist, and post-socialist pe.